PGPR Reduce Root Respiration and Oxidative Stress Enhancing Spartina maritima Root Growth and Heavy Metal Rhizoaccumulation - Mesa-Marín, Jennifer; Del-Saz, Néstor Fernández; Rodríguez-Llorente, Ignacio D.; Redondo-Gómez, Susana; Pajuelo, Eloísa; Ribas-Carbó, Miquel; Mateos-Naranjo, Enrique (Frontiers in Plant Science, 2018)
The present study aims to unravel ecophysiological mechanisms underlying plant-microbe interactions under natural abiotic stress conditions, specifically heavy metal pollution. Effect of Plant Growth Promoting Rhizobacteria (PGPR) bioaugmentation on Spartina maritima in vivo root respiration and oxidative stress was investigated. This autochthonous plant is a heavy metal hyperaccumulator cordgrass growing in one of the most polluted estuaries in the world. The association with native PGPR is being studied with a view to their biotechnological potential in environmental decontamination. As a novelty, the oxygen-isotope fractionation technique was used to study the in vivo activities of cytochrome oxidase (COX) and alternative oxidase (AOX) pathways. Inoculated plants showed decreased antioxidant enzymatic activities and in vivo root respiration rates. The reduction in respiratory carbon consumption and the stress alleviation may explain the increments observed in S. maritima root biomass and metal rhizoaccumulation after inoculation. For the first time, plant carbon balance and PGPR are interrelated to explain the effect of rhizobacteria under abiotic stress.